THE RE-ESTABLISHMENT OF IDEOLOGEME JUSTICE IN "GREY-ZONE" MORAL EMOTIONS OF A RAISING VICTORIAN IDEOLOGY - Iryna Pinich (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
The study investigates into the impetus of grey-zone moral emotions underlying the sustenance of intragroup power relations in the times of ideological transitions of the late 18th and early 19th centuries refracted in the fiction discourse of the pre-Victorian era. The article is based on the assumption that the lingual representation of emotional experiences defines the emotional conceptual structure of the people and establishes social rules for emotion display patterns. A qualitative content analysis of the pre-Victorian novel corpus has substantiated the working hypothesis about the transitory mechanisms of ideological shifts facilitated by the dominant emotional repertoire across the social groups of the time. The paper claims the centrality of justice concerns in the ideological potency of the emotional experience of envy, jealousy, resentment, and ressentiment. An in-depth co-occurrence analysis of lingual representation of justice-seeking emotional reactions testifies to re-establishment of religious ideologeme JUSTICE displayed in a whole-scale procurement of resignation and inhibition compatible with placating vice-related experiences. The study argues that the restoration of the ideologeme under conditions of fixed social stratification is aimed at the exploitation of the emotional kindling of waning religious ideology for the accedence of a newly rising secular Victorian ideology. The analysis of the interconnectedness of lingual representation of grey-zone moral emotional reactions has underpinned the conjecture about their correlation to the system of religious ethics in determining an explicit display of strong feelings of injustice as outward enmity, impiety, and apostasy.